Functions of Theory in an Empirical Study - Krzysztof Rubacha (Nauki o Wychowaniu, 2025)
This article describes three functions of theory in the process of empirical investigation. The first step involves defining the theory. The second identifies and explains its role in the process of forming a research problem, illustrating how theory links the empirical field to the scientific explanations sought. The third step discusses the role of theory in the operationalization process, emphasizing the relationship between theoretical and observational terms, as well as the formulation of research questions and hypotheses, justifying their observational language. Additionally, it is shown that interpretation can potentially transform the theory itself. The article is a presentation of the author’s way of thinking about the relationships between theory and empirical research in the methodology of social research.